x^2 - 3x = - 6x - 1
Then I did this
x^2 - 3x + 6x +1 to get
x^2 +3x +1= 0
a=1. b = 3, c = 1
so I did this
x = -3 +/- sq rt [3^2 - 4(1)(1)] / 2(1) to get
x = -3 +/- sq rt [9 - 4] / 2 then
x = -3 +/- sq rt [5] /2
you can't square it so is this the answer?
Help??
Then I did this
x^2 - 3x + 6x +1 to get
x^2 +3x +1= 0
a=1. b = 3, c = 1
so I did this
x = -3 +/- sq rt [3^2 - 4(1)(1)] / 2(1) to get
x = -3 +/- sq rt [9 - 4] / 2 then
x = -3 +/- sq rt [5] /2
you can't square it so is this the answer?
Help??